Comparing RAMA-LVO with other Prehospital Large-Vessel Occlusion Prediction Scales in Suspected Acute Stroke; A Retrospective Cross-sectional Study - Charascharungkiat, Torntarn; Wangviboonchai, Varaporn; Yuksen, Chaiyaporn; Tienpratarn, Welawat; Palee, Chantarat; Jenpanitpong, Chetsadakon (Archives of Academic Emergency Medicine, 2026)
Introduction: Stroke is a leading global cause of disability, with large-vessel occlusion (LVO) representing a significant proportion of ischemic strokes and requiring timely endovascular thrombectomy (EVT) for optimal outcomes. This study aimed to validate and compare RAMA-LVO with other prehospital LVO prediction scales. Methods: This retrospective, single-center diagnostic accuracy study included adult patients who were triaged as suspected acute stroke in the emergency department (ED) of a university hospital. Four prehospital LVO prediction scales including RAMA-LVO, Rapid Arterial oCclusion Evaluation (RACE), Field Assessment Stroke Triage for Emergency Destination (FAST-ED), and Los Angeles Motor Scale (LAMS) were calculated from documented neurological assessments and compared against confirmed vascular imaging findings. Diagnostic performance was evaluated using the area under the receiver operating characteristic curve (AUROC), with comparative analysis by DeLong’s test and calibration plots to assess model fit. Results: Of the 1,463 patients with suspected acute stroke, 853 patients met the inclusion criteria, with 124 (14.54%) confirmed to have large-vessel occlusion (LVO), most commonly involving the M1 segment of the middle cerebral artery. Patients with LVO were older (p < 0.001), had higher National Institutes of Health Stroke Scale (NIHSS) scores (p < 0.001), and were more likely to receive intravenous thrombolysis or endovascular thrombectomy (p < 0.001) compared with non-LVO patients. Among the four prehospital LVO scales, FAST-ED showed the highest discriminative performance (AUROC = 0.873), closely followed by RAMA-LVO (AUROC = 0.858), while RAMA-LVO demonstrated the highest sensitivity but slightly lower specificity relative to other scales. Conclusion: The RAMA-LVO score demonstrated strong accuracy for identifying acute LVO stroke, comparable to FAST-ED, and may serve as a practical prehospital triage tool for directing patients to thrombectomy-capable centers, especially in regions with transfer delays.